MONITORING AND MANIPULATING ELECTRICAL SYSTEMS USING ARDUINO AND INTERNET OF THINGS (IOT) - Hastuti, Dwi; Prio Budi Santoso, Muhammad; Rifki Ardi Nawan (Universitas PGRI Adi Buana Surabaya, 2022)
The number of jobs in the Ro.nde carbon workshop makes the electricity consumption in the workshop is also large, and also the lack of awareness in the use of electricity in the workshop makes the electricity cost in the workshop large and unstable because of the lack of monitoring of power consumption can not be avoided , sometimes forget to turn off the lighting workshops, ovens, and everyday tools when not in use . That way the researchers made a tool that could monitor the use of electric power and can also control several load points that can be disconnected through the android application using the Internet of things. The method used is monitoring and controlling the use of electric power in the workshop so that things do not happen that are not planned I want to use the Android application using the Internet of Things that has been connected to the Arduino NoeMCU ESP8266 module. This research aims to reduce the risk that might occur due to negligence in the use of electrical loads in the workshop. Researchers hope that this tool can help stabilize electricity consumption in the workshop and avoid things that can harm the workshop itself.